2020
DOI: 10.1029/2019gl086321
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Atmospheric, Oceanic, and Coupled Processes to North Pacific and North Atlantic Variability

Abstract: Patterns of sea surface temperature (SST) variability over the northern oceans arise from a combination of atmospheric, oceanic, and coupled processes. Here we use a novel methodology and a suite of observations to quantify the processes contributing to the dominant patterns of interannual SST variability over these regions. We decompose the upper ocean heat content tendency associated with such dominant patterns into contributions from different heat fluxes: (a) atmospherically driven, (b) surface feedbacks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Marine boundary layer (MBL) clouds exert robust control over the Earth's radiation budget, as they have a prominent spatiotemporal presence and reflect incoming shortwave radiation, thereby cooling the Earth's surface (e.g., L’Ecuyer et al., 2019). Changes in the cloud radiative effect (CRE, for shortwave radiation defined as the difference of the cloud albedo from clear sky) due to climate change can impact the magnitude and persistence of surface temperature anomalies through cloud radiative feedbacks (Gettelman & Sherwood, 2016; Myers & Mechoso, 2020). Aerosols that serve as cloud condensation nuclei (CCN) for these clouds have the potential to alter the CRE as they can change cloud number concentration, cloud liquid water, and, in turn, cloud optical thickness and sky cover.…”
Section: Introductionmentioning
confidence: 99%
“…Marine boundary layer (MBL) clouds exert robust control over the Earth's radiation budget, as they have a prominent spatiotemporal presence and reflect incoming shortwave radiation, thereby cooling the Earth's surface (e.g., L’Ecuyer et al., 2019). Changes in the cloud radiative effect (CRE, for shortwave radiation defined as the difference of the cloud albedo from clear sky) due to climate change can impact the magnitude and persistence of surface temperature anomalies through cloud radiative feedbacks (Gettelman & Sherwood, 2016; Myers & Mechoso, 2020). Aerosols that serve as cloud condensation nuclei (CCN) for these clouds have the potential to alter the CRE as they can change cloud number concentration, cloud liquid water, and, in turn, cloud optical thickness and sky cover.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is widely recognized that AMV involves a complex array of local and regional interactions which are different between the subpolar and tropical regions. In the tropical North Atlantic, processes including changes in wind, evaporation, and clouds (Bellomo et al., 2016; Brown et al., 2016; Martin et al., 2014; Middlemas et al., 2019; Myers & Mechoso, 2020; Sutton et al., 2018), as well as local radiative forcing due to atmospheric composition changes (Booth et al., 2012; Yuan et al., 2016), are thought to be particularly important. In the subpolar region many studies have identified AMOC variability as a key driver of low‐frequency SST and heat content anomalies (Delworth et al., 2017; Robson et al., 2012, 2016; Yeager et al., 2012) as well as long‐term externally forced change (Caesar et al., 2018; Drijfhout et al., 2012).…”
Section: Introductionmentioning
confidence: 99%